Hypoglycaemia as a new cardiovascular risk factor - Rogowicz, Daniel; Wołowiec, Łukasz; Gilewski, Wojciech; Chudzińska, Małgorzata; Zukow, Walery; Sinkiewicz, Władysław (Journal of Education, Health and Sport, 2017)
The World Health Organization (WHO) recognized diabetes as one of the four most important and priority health issues out of non-communicable diseases. According to a report by the WHO with the year 2016 the prevalence of diabetes for 3 decades and continues to grow, this problem applies to the entire world. In 2014. the number of diabetes patients brought the 422 million, by comparison, in 1980. It was 108 million. A badly aligned metabolically diabetes contributes to the development of numerous complications of micro-and macro-angiopathic, which are related to adverse prognosis and increase the risk of cardiovascular disease. Striving for the best possible alignment of the carbohydrate economy reduces both the mortality and cardiovascular. However, some patients with diabetes intensive glucose control is not effective and increases the incidence of severe hypoglycemia, which in turn some patients increases cardiovascular mortality. The aim of the work is the appearance of hypoglycemia as a factor that increases the risk of death in cardiovascular diseases. The work also emphasises the importance of cardiovascular diseases in diabetes, which are the most common complication of diabetes and the most common cause of death in this group of patients.